“Aplicación del principio de oportunidad en las infracciones flagrantes en los delitos de ataque o resistencia en contra de los miembros de la Policía Nacional - Yolanda Beatriz, Gualán Valente (2020)
The principle of opportunity in Ecuadorian criminal legislation is planned as a mechanism for decongestion criminal proceedings, either in its preliminary investigation phase or in the prosecutor phase , a request made by the Prosecutor's Office in the exercise of its powers, which in spite of having materialized the infraction, the prosecution by the State is broken, privileging the increase of impunity and the feeling of lack of justice that the members of the Police Department in active service feel, when they are in flagrant offenses of attack or resistance and therefore excessive regulation in their control intervention when they capture the offenders in flagrant crimes against the members of the Police Department, weakening their capacity of impart order , causing a serious crisis in criminal justice. In Unit I: Topic: The principle of opportunity in flagrant offenses of attack or resistance in the Ecuadorian criminal system; different doctrinal concepts of both the principle of opportunity and the flagrant crime are known, the characteristics of the criminal type of the offense of attack or resistance are found in the Integral Organic Criminal Code that is found inside the crimes against efficient public administration, so that the typicity is composed of objective and subjective elements within the field of criminal law to describe punishable conduct. In Unit II: SUBJECT: Incidence caused by the application of the principle of opportunity in flagrant offenses of attack or resistance; considered as a mechanism for decongestion of the criminal system covered by the principle of minimum criminal intervention, it is at the discretion of the prosecution to continue or not to pursue the criminal action. In Unit III: Topic: The interpretation of the evil called progressive or rational use of force; when speaking of rational or progressive force, it is only discussed the set that controls national security by the members of the Police Department in the exercise of their powers, faculty that is restricted because they necessarily have to be justified, in this way the defenders of human rights ignore their work of control that play in the streets' due to their lack of ignorance and also to realize that there is no cooperation from the citizens. In Unit IV: Topic: I will analyze a practical case of Attack or the resistance No. 06282-2019-00229; I will explain the application of the opportunity principle in flagrant offense of attack or resistance, against the servers of the Police Department in the exercise of their functions. Request made by the Prosecutor's Office that, in the exercise of its functions under the principle of objectivity ,request the principle of opportunity, the Prosecutor's Office stated they make the compensation agreement with the victim same that could not have been stipulated ; but this is not a requirement for the principle of opportunity ,the victim can enforce their rights in civil proceedings.